2020
DOI: 10.1177/0976399620938503
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media in Planning Domestic Holidays: A Study on Malaysian Millennials

Abstract: This study examines the social media usage of Malaysian millennials in planning their domestic holidays. This study integrated the theory of planned behaviour (TPB) and technology acceptance model (TAM) variables by adding electronic word-of-mouth (e-WOM), as it is a crucial factor influencing the travel industry nowadays. Data were collected from 301 Malaysians. The results show that e-WOM is the greatest antecedent influencing Malaysian millennials to use social media in planning their domestic holidays. Loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Various researches have found that rapid gifts, discounts and other incentives increase the likelihood of impulse purchases (Dhall & Singh, 2020; Kedia et al, 2020). However, according to Kumari and Bharti (2021), SP tries to build consumer demand and helps customers to purchase a product rapidly (Moorthy et al, 2021). Promotional methods frequently enhance client purchasing decisions in addition to preventing them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various researches have found that rapid gifts, discounts and other incentives increase the likelihood of impulse purchases (Dhall & Singh, 2020; Kedia et al, 2020). However, according to Kumari and Bharti (2021), SP tries to build consumer demand and helps customers to purchase a product rapidly (Moorthy et al, 2021). Promotional methods frequently enhance client purchasing decisions in addition to preventing them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others have addressed the role of cultural worldview in predicting heritage tourists' behavioural intention to visit Hanok Village in South Korea (Lee et al, 2021). Furthermore, Moorthy et al (2021) employed the theory to examine social media usage among Malaysian millennials in planning for their domestic holidays. Thus, such a widespread application of the TPB in behavioural intention studies further validates its relevance in assessing behavioural intention in tourism studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TPB has an additional variable; perceived behavioural control to predict behaviour (Ajzen, 1991). Research in the Malaysia context have extensively utilized subjective norms, behavioural intention and other factors that make up the TPB model (Alam et al, 2019; Kong et al, 2014; Moorthy et al, 2021). The TPB have several limitations and assume that attitude towards behaviour, subjective norms and PBC are the only factors influencing green behaviour (Moorthy et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The TPB argues that the performance of a particular behaviour increases if a consumer has a positive attitude towards that behaviour (Ajzen, 1991). The validity of TPB has been applied in several environmental studies (Alam et al, 2019; Lynne et al, 1995; Sreen et al, 2018), as well as to examine Millennial profiles (Moorthy et al, 2021). The past examination has argued that 40% of empirical studies in green marketing have applied the TPB relating to environmental issues (Klöckner, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%